Love and war : how militarism shapes sexuality and romance - Digby, Tom, 1945- (EBL-Schweitzer, 2014)
Ideas of masculinity and femininity become sharply defined in war-reliant societies, resulting in a presumed enmity between men and women. This so-called battle of the sexes intensifies in tandem with dispositions to fight actual wars. These are among the fascinating discoveries Tom Digby shares in Love and War, which describes the making and manipulation of gender in both militaristic and nonmilitaristic societies and the consequences for men and women in their personal, romantic, sexual, and professional lives. Drawing on cross-cultural comparisons and examples from popular media, including.